ANALYSIS OF GOOD CORPORATE GOVERNANCE, FINANCIAL PERFORMANCE AND SUSTAINABILITY REPORT - Sri Wahjuni Latifah; Muhammad Fahminuddin Rosyid; Lilik Purwanti; Tri Wahyu Oktavendi (Universitas Muhammadiyah Malang, 2019)
This study aims to analysiss and examine the effect of the financial performance and good corporate governance on sustainability report. Financial performance is measured using ROA. Good corporate governance mechanisms used are managerial ownership, independent commissioner board, board of directors and independent audit committee. The population is state-owned companies listed in the Indonesia Stock Exchange during 2011-2014. A purposive sampling method is used as a sampling method and 13 companies are selected as samples. A multiple linear regression analysis using SEM-PLS program is employed as a data analysis tool. The results show that the ROA, the board of directors, and audit committees affect sustainability reports; while managerial ownership and independent board do not affect sustainability reports.